MANAGEMENT OF POSTPARTUM HEMORRHAGE: HISTORICAL ASPECTS - Наталья Владимировна Артымук; Дмитрий Анатольевич Артымук; Татьяна Юрьевна Марочко; Наталья Борисовна Колесникова; Дилангез Бурхониддиновна Хочибоева (The Publishing House Medicine and Enlightenment, 2024)
The purpose of the study is to trace the historical path of development of methods for managing postpartum hemorrhage (PPH) based on the analysis of data from domestic and foreign literature. Materials and methods: The information bases of the PubMed and e-library systems were assessed. Key words (search words): Search words: «postpartum bleeding», «postpartum bleeding/haemorhage». The search depth is 150 years (1849-2024). Research results. As a result of the study, 9104 sources were found: in PubMed - 4597, in e-library - 4507 publications. 9050 sources were excluded from the analysis: lack of a full version of the publication - 2855, opinion/literature review (no own data) - 1187, mismatch by title - 1236, double reports - 2769, lack of historical aspects of the problem - 2003. 54 publications met the search criteria. PPH continues to be one of the leading causes of maternal mortality. The publication presents the main historical aspects of improving PPH management methods. Several decades ago, a set of conservative measures included emptying the bladder, manual examination of the walls of the uterus, applying cold to the lower abdomen, rubbing the abdominal skin with ether, and intrauterine administration of hot and cold solutions. However, many of these techniques were later found to be untenable. Great attention continues to be paid to improving measures for the prevention and treatment of PPH. Currently, preventing their development is of paramount importance among all measures aimed at reducing maternal mortality. Conclusions. Despite the fact that over the years of development of domestic and foreign obstetrics, many measures for the prevention and treatment of PPH have undergone significant changes, a number of techniques continue to be effectively used in a new transformation, but with a higher level of evidence.